HIV-tat protein forms phosphoinositide-dependent membrane pores implicated in unconventional protein secretion - Zeitler, Marcel; Steringer, Julia P.; Müller, Hans-Michael; Mayer, Matthias P.; Nickel, Walter (The journal of biological chemistry, 2015)
HIV-Tat has been demonstrated to be secreted from cells in a phosphatidylinositol 4,5-bisphosphate (PI(4,5)P2)-dependent manner. Here we show that HIV-Tat forms membrane-inserted oligomers, a process that is accompanied by changes in secondary structure with a strong increase in antiparallel β sheet content. Intriguingly, oligomerization of HIV-Tat on membrane surfaces leads to the formation of membrane pores, as demonstrated by physical membrane passage of small fluorescent tracer molecules. Although membrane binding of HIV-Tat did not strictly depend on PI(4,5)P2 but, rather, was mediated by a range of acidic membrane lipids, a functional interaction between PI(4,5)P2 and HIV-Tat was critically required for efficient membrane pore formation by HIV-Tat oligomers. These properties are strikingly similar to what has been reported previously for fibroblast growth factor 2 (FGF2), providing strong evidence of a common core mechanism of unconventional secretion shared by HIV-Tat and fibroblast growth factor 2.
Gesehen am 21.07.2020